VERIFICATION OF SUSPECTED PLAGIARISM/SELF-PLAGIARISM AND WITHDRAWAL OF DOCTORAL DEGREE. ANTI-PLAGIARISM PROGRAMS AND THE VALUE OF SIMILARITY REPORTS - Luminița-Sorina BAROȘ (Challenges of the Knowledge Society, 2025)
In today's world, where information is easily accessible and shared, academic integrity is crucial for maintaining the credibility of educational systems. However, new challenges, such as dealing with plagiarism and self-plagiarism, have made it harder to verify the originality of academic work, especially for doctoral research. Although anti-plagiarism software has been developed to help detect copied content, there are debates about the usefulness and accuracy of these tools. While anti-plagiarism programs are valuable tools, they should be used in conjunction with expert human judgment to ensure that plagiarism is detected accurately. The process of withdrawing a doctoral degree should be carefully considered and only applied in cases of serious misconduct. This paper argues for a balanced approach to verifying academic integrity, where technology supports human expertise, and the focus is on education and promoting ethical research practices. As self-plagiarism becomes a more significant issue, it's important that regulations evolve to address it, ensuring the continued trustworthiness and credibility of academic research.